Analisis Nilai Agama dan Moral Anak Dalam Kegiatan Menonton Film Animasi Islami di TK Al-Huda - Winka Antungo; Nurhayati Tine; Sulastya Ningsih (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to analyze children's religious and moral values during activities involving watching Islamic animated films at TK Al-Huda Kindergarten, South City District, Gorontalo City. The research employed a qualitative method. The subjects of this study were five educators and students, while the object focused on observing how children's religious and moral values were reflected during the activity. Data collection techniques included observation, interviews, and documentation.The results of the study indicated that the inculcation of religious and moral values in children through the activity of watching Islamic animated films at Al-Huda Kindergarten had been implemented effectively. This was evident in children's improved understanding of religious and moral concepts, such as in the religious aspect, where children became accustomed to greeting and responding to greetings, praying before and after activities, practicing prayer every Friday, and memorizing short surahs. Additionally, behaviors such as honesty, social care, responsibility, mutual assistance, and other positive attitudes also developed well.